Study on the effects of different proportional values on gas pressure control: article - Muhajir, Nur Alia; Ishak, Abdul Aziz (2018)
Gas pressure system is self-regulating process that is fast and noisy. This study is carried out to determine the process characteristics, mode of control and the effects on response curve when three different proportional (P) values are implemented into a gas pressure control system. The process characteristics are determined by using reformulated tangent method while the mode of control is by using Ziegler-Nichols tuning rules. Both of these are done based on the response curve from conducting open loop test while the effects of proportional (P) values are from conducting load disturbance test. As a result, , 0.0355 1/s response rate, 1.3043 s time dead and 32.3478 s time constant are obtained. From the tuning rule, 4.9599 proportional (P) value and 4.3433 s integral (I) value are determined. Lastly, the process took 79.30 s to become stable when an increased proportional (P) value is used, 59.35 s when a decreased value is used and 63 s when there are no change in proportional (P) value. In conclusion, higher proportional (P) value took longer time for the process to stabilize.